Relating Sodium Percentage to Sodium Adsorption Ratio and its Utility in the Northern Great Plains. Issue 4 (12th June 2015) - DeSutter, T.; Franzen, D.; He, Y.; Wick, A.; Lee, J.; Deutsch, B.; Clay, D.
Abstract : Saturated paste derived sodium adsorption ratio (SARe) is not a routine procedure for soil testing laboratories in the northern Great Plains. The objective of this study was to determine the relationship between SARe, a solution‐phase only extraction, and percentage of Na (%Na; Na/(Na+Ca+Mg+K), a solution phase plus exchange phase value using 1M ammonium acetate as an extractant. From the analysis of 1974 soil samples from the northern Great Plains, simple‐linear and quadratic regressions were highly significant at predicting SARe from %Na data. Removal of outliers only slightly increased r 2 values for both models. We found that using %Na from a routine soil test is acceptable for assessment of soil Na levels to help make soil management decisions.